Notary Liability for The Deed of General Meeting of Shareholders of Limited Liability Companies Against The Law (Analysis of Decision Number 123 / PDT. G-Interven/2019/PN. MKS) - Benavita Aprilia Kurnia; Teddy Anggoro (IHSA Institute, 2022)
Abstract Notary is a public official who has the authority to make an authentic deed. An authentic deed as regulated in Article 1868 of the Civil Code is a deed made in the form determined by law by or before a public official authorized to do so at the place where the deed was made. Based on the Law on Notary Positions, a Notary is a public official who is authorized to make an authentic deed and has other authorities as referred to in this Law or based on other laws. This study discusses the Notary's Responsibility for Unlawful Acts in making the deed of the general meeting of shareholders of a limited liability company. The research method used is juridical-normative research which refers to the use of written legal norms contained in statutory regulations. The data used in conducting research and collecting data is secondary data, namely as data obtained directly through tracing Court Decisions, library materials, document studies and interviews. The typology of this research is descriptive so that the results of this study are analytical. This study found that the authentic deed made by a notary that contained elements of forgery and fraud was void. The notary may be subject to administrative sanctions based on UUJN ranging from verbal reprimand, writing, temporary dismissal and disrespectful dismissal. In addition, the Notary can also be held accountable based on unlawful acts in a civil manner in accordance with Article 1365 of the Civil Code and forgery of letters based on the Criminal Code.